Lucíola, Ana Karênina e A Dama das Camélias no Vale das Lágrimas na literatura e no cinema. - Nath, Silvana (2011)
This study is lined on literary and filmic Anna Karenina, The Lady of the Camellias and Luciola, in which settles the relationship between their respective characters with pictures of some women considered saints by the catholic church, whose cutting focuses on themes of love, pain, tears, memory, forgetting, ecstasy and death. We seek to understand how the pain and tears are feelings that produce ambiguity in his senses, because while they reported suffering also expressed pleasure, joy and ecstasy. The pain is bound the memories of the past, or is the manifestation of memory in their minds by showing them the impossibility of permanence, or even future in society to which they belong. On the other hand, this also causes them feeling happy and ecstasy to visualize themselves as victims of the social environment. Analyse the image of women suffering, whose suffering comes from unrequited love, or even the inability to love and be loved in a complete and integrated. Renounce love, but the manifestation of the memory torments and carries its own self-punishment, because the trials and tribulations leading characters to self-condemnation that triggers recall, this represents traces the process of forgetting, by which they must pass to be delivered from sin and purified by love. To achieve oblivion in its completeness that need to undergo the death, in this context will also be undertood as the morality of society, in wich the heroine must die to not tarnish the image of the other women in the social context to which they belong. Finally, the analysis of this research focuses on the intersection between the female characters found in different works of art, namely, the literary, filmic, paintings and sculptures that allow us to examine and reflect upon the themes of pain and tears, death and the manifestation of memory and forgetfulness in different social and historical contexts involving different characters, in order to understand how the tears and pain performing the cleansing power by bringing them hope and regeneration of life after death, according to preach catholicism.